2012
DOI: 10.1254/jphs.11241sc
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration by the Natural Polyamine Spermine of Cartilage and Bone Destruction in Rats With Collagen-Induced Arthritis

Abstract: Abstract. We investigated pharmacological properties of naturally occurring polyamines on cartilage and bone destruction seen in joints of rats with collagen-induced arthritis (CIA). Daily supplementation of spermine (SPM), but not spermidine, significantly inhibited increases in the hind paw volume and arthritis score in CIA rats, in addition to the increased mRNA expression of receptor activator of nuclear factor-κB ligand in both cartilage and synovial tissues. Histological analysis clearly revealed a drast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…One study showed that daily supplementation of spermine significantly inhibited increases in the hind paw volume and arthritis score in collagen-induced arthritis rats. 23 Furthermore, a recent study evaluated the effects of dietary spermine supplementation on the inflammatory response in piglets. They showed that dietary spermine supplementation can alleviate inflammatory response by regulating the gene expression of signaling molecules related to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that daily supplementation of spermine significantly inhibited increases in the hind paw volume and arthritis score in collagen-induced arthritis rats. 23 Furthermore, a recent study evaluated the effects of dietary spermine supplementation on the inflammatory response in piglets. They showed that dietary spermine supplementation can alleviate inflammatory response by regulating the gene expression of signaling molecules related to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicated that polyamines could instead be beneficial for RA. In fact, spermine ameliorated the destruction of cartilage and bone in the joints of CIA rats [ 120 ]. Moreover, both spermidine and spermine inhibited osteoclast differentiation in vitro and prevented bone loss in vivo in ovariectomized mice [ 121 ], an effect possibly due to the inhibition of migration of pre-osteoclasts during the fusion step [ 122 ].…”
Section: Arginine Metabolism and Ramentioning
confidence: 99%
“…It is well known that the use of polyamines in arthritis could be beneficial for synovial bearing reconstruction and reduce osteolytic activity (Iezaki et al, 2012). Moreover, continuous nociceptive stimulation caused by joint inflammation leads to spinal dorsal horn's neurons hyperexcitability inducing neuropathic pain (Fernihough et al, 2004;Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the root composition it has been reported the presence of alkaloids belonging to the spermidine group (Fu et al, 2008) together with the presence of stachydrine, a more polar alkaloid typical of the caper leaves too (Batanouny and Drissamnauer, 2005;Buckingham, 1994). Interestingly, the use of polyamine alkaloids, as those of the spermidine group, has been suggested as efficacious in arthritis disease (Iezaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%